Theoretical Investigation of the Structural, Spectroscopic, Electronic, and Pharmacological Properties of 4-Nerolidylcathecol, an Important Bioactive Molecule - Renyer A. Costa; Earle Silva A. Junior; Jaqueline de A. Bezerra; Josiana Moreira Mar; Emerson S. Lima; Maria Lucia B. Pinheiro; Diego V. C. Mendonça; Guilherme Braule P. Lopes; Adjane Dalvana S. Branches; Kelson M. T. Oliveira (Journal of Chemistry)
4-Nerolidylcatechol (4NRC), a secondary metabolite described as a potent antioxidant that presents anti-inflammatory, antimalarial, analgesic, and cytotoxic properties, has been receiving prominence in the catechol class. In this work, a theoretical DFT study of the vibrational, structural, and quantum properties of 4-nerolidylcatechol (4NRC) using the B3LYP/6-311G (2d,p) level is presented. The theoretical molecular geometry data were compared with the X-ray data of a similar molecule in the associated literature and a conformational study is presented, with the aim of providing a good comprehension of the 4NRC structural arrangement and stability. Also, HOMO-LUMO energy gap and natural bond orbitals (NBOs) were performed and discussed. The calculated UV spectrum showed similarity to the experimentally obtained data, with transitions assigned. The comparative IR studies revealed that intermolecular hydrogen bonds that stabilize dimeric forms are plausible and also allowed the assignment of several characteristic vibrations. Molecular docking calculations with DNA topoisomerase I-DNA complex (TOPO-I), glyceraldehyde 3-phospate dehydrogenase (GAPDH), and Plasmodium falciparum lactate dehydrogenase (PfLDH) showed binding free energies of −6.3, −6.5, and −7.6 kcal/mol, respectively, which indicates that 4NRC is a good competitive inhibitor for these enzymes.